Preoperative HbA1c > 8% Is Associated With Poor Outcomes in Lumbar Spine Surgery: A Michigan Spine Surgery Improvement Collaborative Study. Issue 5 (November 2021) - Lim, Seokchun; Yeh, Hsueh‐Han; Macki, Mohamed; Mansour, Tarek; Schultz, Lonni; Telemi, Edvin; Haider, Sameah; Nerenz, David R; Schwalb, Jason M; Abdulhak, Muwaffak; Park, Paul; Aleem, Ilyas; et al.
Abstract : BACKGROUND: : Preoperative hemoglobin A1c (HbA1c) is a useful screening tool since a significant portion of diabetic patients in the United States are undiagnosed and the prevalence of diabetes continues to increase. However, there is a paucity of literature analyzing comprehensive association between HbA1c and postoperative outcome in lumbar spine surgery. Objective: : To assess the prognostic value of preoperative HbA1c > 8% in patients undergoing elective lumbar spine surgery. MethodS: : The Michigan Spine Surgery Improvement Collaborative (MSSIC) database was queried to track all elective lumbar spine surgeries between January 2018 and December 2019. Cases were divided into 2 cohorts based on preoperative HbA1c level (≤8% and >8%). Measured outcomes include any complication, surgical site infection (SSI), readmission (RA) within 30 d (30RA) and 90 d (90RA) of index operation, patient satisfaction, and the percentage of patients who achieved minimum clinically important difference (MCID) using Patient‐Reported Outcomes Measurement Information System. Results: : We captured 4778 patients in this study. Our multivariate analysis demonstrated that patients with HbA1c > 8% were more likely to experience postoperative complication (odds ratio [OR] 1.81, 95% CI 1.20‐2.73; P = .005) and be readmitted within 90 d of index surgery (OR 1.66, 95% CI 1.08‐2.54; P = .021). They also had longer hospital stay (OR 1.12, 95% CI 1.03‐1.23; P = .009) and were less likely to achieve functional improvement after surgery (OR 0.64, 95% CI 0.44‐0.92; P = .016). Conclusion: : HbA1c > 8% is a reliable predictor of poor outcome in elective lumbar spine surgery. Clinicians should consider specialty consultation to optimize patients' glycemic control prior to surgery. Graphical Abstract : Figure. Graphical Abstract